Butterfly diversity in natural and modified habitat at Bahorok District, Langkat Regency, North Sumatra: Keanekaragaman kupu-kupu di habitat alami dan habitat buatan di Kecamatan Bahorok, Kabupaten Langkat, Sumatera Utara - Nurhayati; Syarifuddin; Ritonga, Yusran Efendi; Pradwinata, Ricky; Pendong, Lexi Majesty (Jurnal Entomologi Indonesia, 2025)
Changes in the function of natural areas, rice fields, and plantations can reduce the number and diversity of butterflies, with environmental factors playing a significant role in shaping butterfly richness and diversity. This study aimed to identify differences in butterfly diversity and composition between natural and modified habitats and to examine the relationship between environmental factors and butterfly richness and diversity. This research was conducted from March to April 2021 using a modified exploration method (pollard walk) through direct observations of butterflies. Observations were conducted in two sessions from 08:00–12:00 and 13:00–17:00. The results of this study successfully found five butterfly families with 995 individuals in natural habitats (79 species), whereas, in modified habitats, as many as 627 individuals (29 species) were documented. Based on the Shannon Winner index (H’) and Margelaf richness index (R), the natural habitat was classified as high (H’ = 3.84, R = 11.2). Simpson’s index and evenness values of the two habitats were too different and classified as high. There were significant differences in butterfly abundance between the natural and modified habitats (t (164) = 2.441, p = 0.016). Among the biotic factors examined, only wind speed significantly affected butterfly abundance.